Pelatihan Penulisan Karya Tulis Ilmiah kepada Guru-guru di SDN 42 Pekanbaru - Nurul Fauziah; Oktariani Oktariani; Roizawati Roizawati; Rahmawati Rahmawati (Community Education Engagement Journal, 2023)
The aim of this community service activity is to provide training in writing scientific papers to teachers at SDN 42 Pekanbaru. The problem with partners is that there is still a low level of publication of teachers scientific papers in national journals and accredited national journals, especially is scientific publications are one of the main requirements for promotion. Teachers are asked to adapt their PTK research reports to the selected journal template. Starting from the title component to the bibliography. The completed journal will be sent to the speakers email for review before the journal is submitted to each targeted journal. In conclusion, teachers understand how to write scientific papers in journal form, they can contribute to increasing scientific literacy and articles that have been published in scientific journals can have significant benefits in the field of administration, including rank and educational administration.